Patterning, Reading, and Executive Functions - Bock, Allison M.; Cartwright, Kelly B.; McKnight, Patrick E.; Patterson, Allyson B.; Shriver, Amber G.; Leaf, Britney M.; Mohtasham, Mandana K.; Vennergrund, Katherine C.; Pasnak, Robert (Frontiers in Psychology, 2018)
Detecting a pattern within a sequence of ordered units, defined as patterning, is a cognitive ability that is important in learning mathematics and influential in learning to read. The present study was designed to examine relations between first-grade children’s executive functions, patterning, and reading abilities, and to examine whether these relations differ by the type of pattern. The results showed that working memory correlated with reading fluency, and comprehension measures. Inhibition correlated only with the latter. Cognitive flexibility was correlated with patterning performance and with performance on object size patterns, whereas working memory was correlated with performance on symmetrical patterns and growing number patterns. These results suggest that the cognition required for completing patterns differs depending on the pattern type. Teachers may find it beneficial to place emphasis on the switching and working memory components of completing patterning tasks, depending on the type of patterns used in instruction.